2004
DOI: 10.1146/annurev.neuro.27.070203.144157
|View full text |Cite
|
Sign up to set email alerts
|

The Amygdala Modulates the Consolidation of Memories of Emotionally Arousing Experiences

Abstract: Converging findings of animal and human studies provide compelling evidence that the amygdala is critically involved in enabling us to acquire and retain lasting memories of emotional experiences. This review focuses primarily on the findings of research investigating the role of the amygdala in modulating the consolidation of long-term memories. Considerable evidence from animal studies investigating the effects of posttraining systemic or intra-amygdala infusions of hormones and drugs, as well as selective l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

117
1,610
10
33

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,008 publications
(1,770 citation statements)
references
References 212 publications
(201 reference statements)
117
1,610
10
33
Order By: Relevance
“…Hyporesponsive PFC, as well as reduced connectivity to the amygdala (Jin et al, 2013;Shin et al, 2004a) may indicate insufficient inhibitory control over exaggerated fear responses. Lastly, abnormal hippocampal function (Corcoran and Maren, 2001) and reduced connectivity to the amygdala (Dolcos et al, 2004;McGaugh, 2004) may underlie impairments in contextual memory processing and the ability to inhibit intrusive memories (Shin et al, 2004a), although findings have been mixed (Hughes and Shin, 2011). A recent resting-state fMRI study showed increased activity in amygdala and reduced spontaneous neural activity in the dorso-lateral PFC (DLPFC) (Yan et al, 2013).…”
Section: Clinicalmentioning
confidence: 99%
“…Hyporesponsive PFC, as well as reduced connectivity to the amygdala (Jin et al, 2013;Shin et al, 2004a) may indicate insufficient inhibitory control over exaggerated fear responses. Lastly, abnormal hippocampal function (Corcoran and Maren, 2001) and reduced connectivity to the amygdala (Dolcos et al, 2004;McGaugh, 2004) may underlie impairments in contextual memory processing and the ability to inhibit intrusive memories (Shin et al, 2004a), although findings have been mixed (Hughes and Shin, 2011). A recent resting-state fMRI study showed increased activity in amygdala and reduced spontaneous neural activity in the dorso-lateral PFC (DLPFC) (Yan et al, 2013).…”
Section: Clinicalmentioning
confidence: 99%
“…[35][36][37][38][39][40][41] In addition, the amygdala modulates fear-related learning in other brain structures, such as the cortex and hippocampus. [42][43][44][45] Some types of fear conditioning, including the contextual and trace fear conditioning, also involve the hippocampus. [46][47][48][49][50][51] Unlike the hippocampus, the amygdala is necessary for the acquisition of fearful memories and their long-term storage and retrieval.…”
Section: Learning and Memorymentioning
confidence: 99%
“…Importantly, emotional and arousing events are known to be better recollected than neutral events, which is thought due at least in part to the influence of neural and hormonal responses to such events (LaBar & Cabeza, 2006;McGaugh, 2000McGaugh, , 2004. Specifically, stressful and arousing events cause increased release of substances such as glucose, cortisol, and epinephrine (Dickerson & Kemeny, 2004;McCarty & Gold, 1981;McGaugh, 1990McGaugh, , 2000Merali, McIntosh, Kent, Michaud, & Anisman, 1998;Piazza & Le Moal, 1997), which have been repeatedly associated with memory modulation (e.g., Czech, Nielson, & Laubmeier, 2000;LaBar & Cabeza, 2006;McGaugh, 2000;Nielson, Czech, & Laubmeier, 1999;Nielson & Jensen, 1994;van Stegeren, Everaerd, Cahill, McGaugh, & Gooren, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, stressful and arousing events cause increased release of substances such as glucose, cortisol, and epinephrine (Dickerson & Kemeny, 2004;McCarty & Gold, 1981;McGaugh, 1990McGaugh, , 2000Merali, McIntosh, Kent, Michaud, & Anisman, 1998;Piazza & Le Moal, 1997), which have been repeatedly associated with memory modulation (e.g., Czech, Nielson, & Laubmeier, 2000;LaBar & Cabeza, 2006;McGaugh, 2000;Nielson, Czech, & Laubmeier, 1999;Nielson & Jensen, 1994;van Stegeren, Everaerd, Cahill, McGaugh, & Gooren, 1998). These substances act, at least in part, by influencing amygdala function, which then modulates the memory consolidation processes (Adolphs, Tranel, & Buchanan, 2005;Canli, Zhao, Brewer, Gabrieli, & Cahill, 2000;Kensinger & Corkin, 2004;McGaugh, 2004). Importantly, memory modulatory effects can be generated during or after learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation